A Discussion of Pricing Strategy for a Community Based Business in UK—The Angler’s Rest - Xu, Silin (2017)
The importance on how to develop an appropriate pricing strategy is increasing in recent year. This paper will discuss pricing strategy in the market of food and drinking and choose Angler’s rest as a case study. The primary objective of this paper is to discuss how pricing strategy can be applied to improve the performance for the Angler’s Rest, in terms of profit improvement, enhance the popularity of consumers. The review is structured around the following topics: the basic pricing method, the attitudes toward pricing and pricing strategy for the perspective of the company, consumer, and competitor, and the list of pricing strategy. In the case study, this paper analyzes Angler’s rest from the company, consumer, and competitor, using secondary data to finish a basic analysis. Based on the theoretical and practical analysis, this paper offers some recommendations for Angler’s rest to develop a better pricing strategy.